Food-borne parasitoses in Malaysia epidemiological assessment and research needs. - Shekhar, K.C. (1995)
Food-borne parasitic zoonoses have emerged as a major public health problem in many countries and are posing a medical challenge. They are not only important from the economic point of view but also because of their severe sequelae. In Malaysia, these parasitoses are a tip of an iceberg problem. The article documents all the food-borne parasitic zoonoses reported in Malaysia. An epidemiological assessment of the diseases with research needs is highlighted.